From Exclusivism to Pluralism: A Reflection on European Religious Minorities - Rosca, Mariana (The Age of Human Rights Journal, 2018)
This paper reviews the religious diversity theory in the writings of Hick, Legenhausen and Netland, among others. It distinguishes two main approaches to religious diversity, pluralism and exclusivism, and examines their negative and positive application in the current situation of new minorities’ management policies. Drawing on current praxis the negative consequences of religious minorities’ disintegration processes are identified. The paper argues for the need to develop further actions that could effectively accommodate minority´s religious identities, in order to build a common and shared framework, with a certain degree of flexibility to be able to adapt to future social and cultural changes.